“The relationship between account payable and company performance” / Farah Wahida Jasmin - Jasmin, Farah Wahida (Faculty of Business and Management, 2009)
Account Payable is the gatekeeper of the organization’s funds. Without AP best practices, there’s a risk of “leakage” of those funds through duplicate or erroneous payments, missed invoice discounts, late-payment penalties, misuse of funds, and outright fraud. The issues that would like to highlight in this study is regard whether this company adapt the actual theories of account payable management in their operation and how well the company’s account payable management operates toward company performance. The data of this study are gathered from both primary and secondary data. Ratio analysis has been used to compare the company performance for five years. It has been identified in the findings that the company has adapted the actual theories of account payable in their operation. However, a further study need to be carried on because the account payable functions have changed radically over the past decade and this transformation continues. Base on the result of this study, some recommendation has been proposed which hopefully can help them to improve their business performance in the future.